Platelet Adhesion in Polytetrafluoroethylene (PTFE) Vascular Grafts In Vivo and the Influence of Increased Intramuscular Pressure-An Experimental Model - Christenson, J T; Qvarfordt, P; Strand, S-E; Arvidsson, D; Sjöberg, T; Olsson, P-I (Thrombosis and Haemostasis, 1983)
Thrombogenicity of graft material is involved in early graft failure in small diameter grafts. The frequently seen postoperative swelling of the leg after distal revascularization may cause an increased intramuscular pressure and early graft failure.Pairs of 4 mm polytetrafluoroethylene (PTFE) grafts were implanted. Autologous platelets were labeled with mIn-oxine. Platelet adhesiveness onto the grafts were analyzed from gamma camera images. Intramuscular pressures were measured with wick technique. Blood flow was measured. One graft served as control the other as test graft. Ninety minutes after declamping the i. m. pressure was increased in the test-leg to 30 mmHg, and later to 60 mmHg.In the control-graft platelet uptake increased to a maximum 60 min after declamping. Blood flow and i.m. pressure remained uneffected. The test-grafts were initially similar but when i.m. pressure was increased to 30 mmHg activity in the grafts increased significantly. Blood flow decreased with 12% of initial flow. When i. m. pressure was raised to 60 mmHg platelet uptake continued to increase.An increased intramuscular pressure of 30 mmHg or more significantly increase the amount of platelets adhering onto PTFE grafts, emphasizing the need for measuring intramuscular pressures after lower limb vascular revascularizations.
Keywords: Intramuscular pressure; 111In-oxine; Platelet adhesion; Arterial grafts